2018
DOI: 10.3389/fpsyg.2018.00157
|View full text |Cite
|
Sign up to set email alerts
|

Learning and Recall of Medical Treatment-Related Information in Older Adults Using the Differential Outcomes Procedure

Abstract: It has recently been reported that the differential outcomes procedure (DOP) might be one of the therapeutical techniques focused at promoting autonomy in the elderly to deal with their medical issues. Molina et al. (2015) found that a group of healthy young adults improved their learning and long-term retention of six disorder/pill associations when each relationship to be learned was associated with a particular reinforcer (the differential outcomes condition) compared to when they were randomly administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
0
9
2
Order By: Relevance
“…Memory tests were conducted 1 hour and 1 week after the learning training sessions. On the basis of the results observed by Molina et al [30] and Plaza et al [31], as well as those of other studies that have shown long-term memory improvements under the DOP (e.g., [28,32,33]), we hypothesized that patients with AD will show improved learning and long-term retention of the learned associations when they are trained with the DOP compared to when they are trained with the NOP.…”
Section: Plos Onementioning
confidence: 85%
See 2 more Smart Citations
“…Memory tests were conducted 1 hour and 1 week after the learning training sessions. On the basis of the results observed by Molina et al [30] and Plaza et al [31], as well as those of other studies that have shown long-term memory improvements under the DOP (e.g., [28,32,33]), we hypothesized that patients with AD will show improved learning and long-term retention of the learned associations when they are trained with the DOP compared to when they are trained with the NOP.…”
Section: Plos Onementioning
confidence: 85%
“…The results indicated that, compared to the standard or non-differential outcomes procedure (the NOP), when each to-be-learned association was reinforced with a unique outcome (the DOP), participants showed higher percentage of correct responses, needed fewer trials to learn the associations, and demonstrated greater long-term retention of the information that was previously learned. In a recent follow-up study, Plaza, Molina, Fuentes, and Estévez [31] demonstrated that healthy older adults also benefited from the DOP when the to-be-learned association was between a particular pill and the time of the day the participants had to take it according to a prescribed schedule. The benefits of the DOP extended also to performance in a recognition memory test that took place one week later.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…With an alpha = .05 and power = .80, the analysis revealed that thirty-six participants were required to detect a small-medium effect size (d=0.44). The effect size expected is based on previous studies concerning to the DOP in healthy adults (e.g., Plaza et al, 2018). Participants were tested individually in quiet rooms with identical sound and lighting conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have demonstrated that the DOP is effective in optimizing discriminative learning and visuospatial recognition memory in healthy people (e.g., Easton, 2004;Esteban, Vivas, Fuentes, & Estévez, 2015;Estévez et al, 2007;López-Crespo, Plaza, Fuentes, & Estévez, 2009;Martínez, Estévez, Fuentes, & Overmier, 2009;Miller, Waugh, & Chambers, 2002;Mok & Overmier, 2007;Molina, Plaza, Fuentes, & Estévez, 2015;Plaza, Estévez, López-Crespo, & Fuentes, 2011;Plaza, Molina, Fuentes, & Estévez, 2018). The DOP also helps to improve the same cognitive processes in populations with neurocognitive deficits (e.g., Carmona, Vivas, & Estévez, 2019;Esteban, Plaza, López-Crespo, Vivas, & Estévez, 2014;Estévez, Fuentes, Overmier, & González, 2003;Hochhalter, Sweeney, Bakke, Holub, & Overmier, 2000;Joseph, Overmier, & Thompson, 1997;Martínez et al, 2012;Plaza, López-Crespo, Antúnez, Fuentes, & Estévez, 2012).…”
mentioning
confidence: 99%